2015
DOI: 10.1089/ten.tea.2013.0671
|View full text |Cite
|
Sign up to set email alerts
|

A Nanomedicine Approach to Effectively Inhibit Contracture During Bladder Acellular Matrix Allograft-Induced Bladder Regeneration by Sustained Delivery of Vascular Endothelial Growth Factor

Abstract: Macroscopic evidence of contracture has been identified as a major issue during the regeneration process. We hypothesize that lack of angiogenesis is the primary cause of contracture and explore a nanomedicine approach to achieve sustained release of vascular endothelial growth factor (VEGF) to stimulate angiogenesis. We evaluate the efficacy of poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) for long-term (3 months) sustained release of VEGF in bladder acellular matrix allografts (BAMA) in a swine mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Most studies on the urinary bladder have focused on VEGF as some propose that vascularization is the limiting step for a functional bladder. Incorporating VEGF has been shown to increase angiogenesis, increase muscle regeneration and affect urothelial ingrowth [115][116][117][118][119]. However, its effect on the urothelium per se in these tissue engineering studies is still not fully understood [115,116,118,120].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the urinary bladder have focused on VEGF as some propose that vascularization is the limiting step for a functional bladder. Incorporating VEGF has been shown to increase angiogenesis, increase muscle regeneration and affect urothelial ingrowth [115][116][117][118][119]. However, its effect on the urothelium per se in these tissue engineering studies is still not fully understood [115,116,118,120].…”
Section: Discussionmentioning
confidence: 99%
“…[112] Xiong et al also showed a successful action of VEGF-loaded PLGA nanoparticles in the promotion of blood vessels and smooth muscle fibers regeneration, in the bladder of a swine model, and that the nanoparticles were able to release VEGF for at least 3 months. [113] Despite all the advantages concerning PLGA-based DDSs, there are still some issues to be overcome when nanoparticles are administered, especially into bloodstream. The main problem during PLGA nanoparticles administration is their interaction with the circulating proteins, producing different protein corona profiles.…”
Section: Poly(lactic-co-glycolic) Acid Nanoparticlesmentioning
confidence: 99%
“…Another possible approach to stimulate bladder regeneration in vivo could be based on application of various agents (eg, cytokines, growth factors) that promote cellular ingrowth from the native bladder wall. [44][45][46] Thus, in the recently published study by Xiong et al the authors introduced vascular endothelial growth factor-loaded poly(lactic-co-glycolic acid) nanoparticles for long-term sustained release in bladder acellular matrix allografts in a swine model. 44 Implantation of this scaffold resulted in increased angiogenesis that reduced contracture during bladder regeneration.…”
mentioning
confidence: 99%
“…44 Implantation of this scaffold resulted in increased angiogenesis that reduced contracture during bladder regeneration. 44 …”
mentioning
confidence: 99%